Comparison of elastic properties for different sample types fabricated with additive manufacturing - Moon, Seung Ki (2018)
Additive Manufacturing (AM), also known as 3D printing, is a technology where successive layers of material are deposited one on top of the other to form parts. AM has a high degree of design flexibility and allows the fabrication of highly customized parts in a short amount of time, making it ideal for industries such as aerospace. The mechanical properties of 3D printed materials, especially those produced via Fused Deposition Modelling (FDM), are dependent on many factors, making standardization difficult. Thus far, only a handful of standards have been created specifically for AM so most of the research still relies on previous standards. These old standards generally assume isotropic materials, which makes the results obtained through their use not entirely accurate since 3D printed materials usually have a high degree of anisotropy. This paper is dedicated to the study of the differences in the elastic moduli measured with two different types of coupons designed using ASTM standard D638. Comparison of the values measured for each type of sample shows that the sample geometry does not make a difference when testing 3D printed materials.